Model Pembelajaran Passing Sepak Bola Menggunakan Teaching Games For Understanding (TGFU) di Sekolah Menengah Kejuruan - Ragil Wiryawan, Muhammad; Prabowo, Eko; Ginanjar, Shela (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This study aims to design a soccer passing learning model using Teaching Games For Understanding (TGFU) in Vocational High Schools. The methodology used in this study is Research and Development (R&D) which focuses on designing models and validating soccer passing learning models using Teaching Games For Understanding (TGFU) in Vocational High Schools. This study uses the ADDIE model (Analyze, Design, Development, Implementation, Evaluate) because it has systematic, simple, and easy-to-implement stages. The ADDIE model was chosen as a framework because it has been widely applied in previous studies and has a clear work step structure. A total of 18 learning models were designed, then went through a validation process by three experts, namely learning experts, soccer experts and physical education teachers. The results of the validation stated that 18 learning models were declared valid and met the eligibility criteria to be applied in learning, and based on the results of the questionnaire on the ease of the model that had been filled out by students, 184 (28.4%) said the model was very easy, 390 (60.2%) said easy mode, 73 (11.3%) said the model was less easy, 1 (0.1%) said the model was not easy. In general, the soccer passing learning model using Teaching Games For Understanding (TGFU) was declared feasible to be implemented in Vocational High Schools.